Architecture changing spatial transitions between context, construction and human activities - Deepak, B. B. V. L. (Singapore Springer, 2021)
The question of what architecture is answered in this book with one sentence: Architecture is space created for human activities. The basic need to find food and water places these activities within a larger spatial field. Humans have learned and found ways to adjust to the various contextual difficulties that they faced as they roamed the earth. Thus rather than adapting, humans have always tried to change the context to their activities. Humanity has looked at the context not merely as a limitation, but rather as a spatial situation filled with opportunities that allows, through intellectual interaction, to change these limitations. Thus humanity has created within the world their own contextual bubble that firmly stands against the larger context it is set in. The key notion of the book is that architecture is space carved out of and against the context and that this process is deterministic.
Electronic reproduction
Keywords: Building